Integration of IoT into security systems: opportunities and risks - Sotnik, S. (International Journal of Academic Engineering Research (IJAER), 2024)
The paper reveals conceptual aspects of security systems transformation through introduction of IoT technologies. The study includes critical analysis of innovative approaches to security using smart devices and network solutions. The paper presents architecture of modern IoT mechanisms, demonstrates methodology for assessing technological capabilities and potential challenges in field of cybersecurity. The focus is on comprehensive study of interaction of various components: from sensors and communication protocols to cloud platforms and artificial intelligence systems. The key goal of study was to identify strategic directions for development of IoT echnologies, mechanisms for countering threats, and prospects for improving security systems. The presented scientific results provide holistic view of evolution of approaches to security in context of digital transformation. The scientific novelty of work lies in systematic analysis of potential of IoT solutions, substantiation of risk minimisation methods and disclosure of innovative strategies for introduction of intelligent technologies in security sector.
Keywords: risks; IoT technologies